A Delphi method to classify wave energy resource for the 21st century: Application to the NW Iberian Peninsula. (15th November 2021) - Ribeiro, A.S.; deCastro, M.; Costoya, X.; Rusu, Liliana; Dias, J.M.; Gomez-Gesteira, M.
Abstract: Wave energy is poised to thrive as a renewable energy provider. Present and future wave energy resource for the northwest Iberian Peninsula coast is classified by means of a dynamical downscaling performed with the SWAN model of WAVEWATCH III simulations driven by historical wind data and future wind under the RCP8.5 greenhouse gas emission scenario. The wave energy resource classification was performed applying a Delphi method to seven indices, related to wave resource, stability, risk and installation and maintenance costs (mean wave power energy, temporal and monthly variability, downtime, risk, water depth and distance to the coast). In general, conditions for the exploitation of wave energy will worsen by the end of the century due to the decrease in wave energy's mean value and an increase in energy variability. Furthermore, the risk factor will also worsen due to the increase in the frequency of extreme ocean waves. Despite this, the wave energy resource will be classified as excellent along the west coast of the Iberian Peninsula and as good along the Bay of Biscay's coast by the end of the century. Only in the northwest corner of the Iberian Peninsula, the wave resource will be classified as outstanding. Highlights: Classification of present and future wave energy resource based on a Delphi method. Delphi applied to factors related to wave energy resource, stability, risk and cost. SWAN dynamical downscaling of present and future wave properties ( H s, T p ). On average, future conditions for the exploitation of wave energy will worsen.